Role of Systemic Inflammation in Linking Psoriasis with Pulmonary Function Decline A Case-Control Study - Nighat Fatima, Kashif Sardar, Saba Amin, Sufyan Saleem Safdar, Bakhtawar Farooq, Zahid Habib Qureshi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Psoriasis is an immune mediated inflammatory chronic disease with several systemic complications. Chronic systemic inflammation might be associated with pulmonary dysfunction via cytokine-mediated airway inflammation and respiratory tissue damage. Objective: To assess inflammatory biomarkers and spirometric parameters in order to assess the role of systemic inflammation as a connecting link between psoriasis and pulmonary function decline in patients with psoriasis. Methods: The study was a case-control study, carried out at the Department of Dermatology and Department of Pulmonology, Multan Medical & Dental College, Multan, Punjab, Pakistan, between March 2022 and March 2023. A total of 100 participants were enrolled, including 50 clinically diagnosed psoriasis patients and 50 healthy controls. Demographic and clinical data were collected such as smoking status, body mass index, disease duration and PASI (Psoriasis Area and Severity Index) score. The levels of serum inflammatory markers such as C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) were assessed. Pulmonary function testing using computerized spirometry was carried out. SPSS version 26.0 was used for statistical analysis. Results: The levels of inflammatory biomarkers were significantly higher in psoriasis patients than in healthy controls. Mean CRP, ESR, IL-6, and TNF-α levels were markedly higher in psoriasis patients (p<0.001). Pulmonary function parameters including forced expiratory volume in one second (FEV1), forced vital capacity (FVC), FEV1/FVC ratio, and FEF25–75% were significantly reduced among psoriasis patients compared with controls (p<0.001). There were significant negative correlations between high inflammatory biomarker levels and the pulmonary function parameters. In multivariate regression analysis, CRP, IL-6, smoking status, BMI and PASI score were all independent predictors of pulmonary function decline. Conclusion: There is strong association between psoriasis and pulmonary function impairment or with increased systemic inflammatory biomarkers. Long-term systemic inflammation could be a key contributor to respiratory impairment in psoriasis patients. Early pulmonary evaluation and inflammatory monitoring can help to minimise the long-term respiratory complications. Keywords: Psoriasis; systemic inflammation; pulmonary function decline; spirometry; IL-6; TNF-α; CRP; pulmonary impairment.